Curcumin-loaded Janus wound dressing based on femtosecond laser and preparation method thereof

The curcumin-loaded Janus wound dressing prepared by femtosecond laser processing and reverse molding process solves the problem that existing dressings are prone to bacterial adhesion when providing a humid environment, and achieves accelerated wound healing and reduced infection risk by improving the drug loading and antibacterial properties of curcumin.

CN119838041APending Publication Date: 2025-04-18BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083663.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

While providing a humid environment, existing wound dressings tend to lead to bacterial adhesion and growth, increasing the risk of infection, and the low water solubility and poor stability of natural antibacterial compounds such as curcumin limit their application.

Method used

Femtosecond laser processing technology was used to prepare PDMS matrix with microgroove structure, and curcumin-loaded Janus wound dressing was prepared through reverse molding process and drug modification, which had asymmetric wetting and good biocompatibility.

Benefits of technology

This dressing can not only effectively reduce bacterial adhesion and growth, significantly improve the drug loading and antibacterial properties of curcumin, accelerate wound healing, but also have good cell compatibility and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838041A_ABST
    Figure CN119838041A_ABST
Patent Text Reader

Abstract

The invention discloses a curcumin-loaded Janus wound dressing based on femtosecond laser and a preparation method of the curcumin-loaded Janus wound dressing, and belongs to the technical field of femtosecond laser processing material preparation. The preparation method comprises the following steps: ultrasonically cleaning a substrate for femtosecond laser processing to obtain a substrate with a micro-groove structure; taking two substrates with the micro-groove structures as templates, oppositely stacking the surfaces with the micro-structures, and filling a prepolymer between the surfaces to obtain a PDMS (Polydimethylsiloxane) substrate with the micro-groove structures on the two surfaces; the preparation method comprises the following steps: taking a chitosan-modified chitosan as a raw material, putting the chitosan-modified chitosan-modified chitosan into a buffer solution, covering the lower surface with an adhesive tape, adhering a layer of polydopamine coating on the upper surface, sequentially putting the chitosan-modified chitosan-modified chitosan-modified chitosan into a curcumin-ethanol solution and a quaternized chitosan solution, rinsing, and carrying out vacuum drying, so as to obtain the curcumin-loaded Janus wound dressing. The invention discloses a curcumin-loaded Janus wound dressing based on femtosecond laser and a preparation method of the curcumin-loaded Janus wound dressing. The curcumin-loaded Janus wound dressing has asymmetric wettability, good biocompatibility, good antibacterial ability and a function of accelerating wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of femtosecond laser processing material preparation, and particularly relates to a femtosecond laser-based curcumin-loaded Janus wound dressing and a preparation method thereof. Background Art

[0002] The skin is the largest organ in the human body and the first line of defense against external environmental damage. It has important functions such as regulating body temperature, protecting internal organs from external influences, and preventing the invasion of exogenous microorganisms. However, in daily life, due to diseases or injuries, the skin barrier may be damaged, causing the underlying tissue to be exposed to microbial contamination, which not only makes wound healing difficult, but also may cause infection and tissue and organ damage, thereby seriously reducing the patient's quality of life. Therefore, wound management has become an important clinical issue, and appropriate wound dressings are an effective means of wound treatment.

[0003] During the wound healing process, maintaining a moist environment on the wound surface plays an important role in promoting cell migration, reducing pain and accelerating healing. However, while providing a moist wound environment, a completely hydrophilic dressing structure may also provide suitable conditions for the attachment and proliferation of external bacteria, thereby increasing the risk of infection. Inspired by the special wettability of certain plants in nature (such as the surface of lotus leaves), studies have found that hydrophobic surfaces with low surface energy can effectively reduce the adhesion and growth of bacteria on materials, thereby inhibiting the formation of biofilms. Therefore, designing a wound dressing with a hydrophilic-hydrophobic asymmetric Janus structure, which has the dual functions of maintaining a moist wound environment and resisting external contamination, has become one of the current hot directions in wound dressing design. However, the antibacterial effect of a single Janus dressing is still limited. In order to further enhance the antibacterial properties, current research focuses on adding antibacterial agents to wound dressings.

[0004] Although antibiotics and antibacterial agents are effective against most bacterial infections, the problem of antimicrobial resistance caused by the abuse of antibiotics is becoming increasingly serious. In recent years, the number of studies using natural antimicrobial compounds has gradually increased, but the low availability and instability of natural compounds themselves limit their widespread application. Curcumin, as a natural polyphenol compound, has attracted great attention in wound anti-infection and anti-oxidation due to its wide range of pharmacological activities such as anti-inflammatory, antibacterial, and antioxidant activities and low risk of drug resistance. However, due to the shortcomings of curcumin itself, such as low water solubility and poor stability, its bioavailability is reduced. Therefore, it is usually necessary to prepare suitable drug carriers for loading and encapsulation. Therefore, it is of great significance to develop a simple, effective, safe and stable curcumin drug delivery carrier dressing as a controlled release of curcumin and improve the antibacterial properties of wound dressings. Summary of the invention

[0005] The present invention aims to provide a femtosecond laser-based curcumin-loaded Janus wound dressing and a preparation method thereof. The curcumin-loaded Janus wound dressing has asymmetric wettability, good biocompatibility, antibacterial ability and the function of accelerating wound healing.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a femtosecond laser-based curcumin-loaded Janus wound dressing comprises the following steps:

[0008] S1, ultrasonically clean the substrate, dry it, and obtain a clean substrate;

[0009] S2, performing femtosecond laser processing on the clean substrate obtained in step S1 to obtain a substrate with a micro-groove structure;

[0010] S3, taking two sheets of substrates with micro-groove structures obtained in step S2 as templates, stacking the surfaces with micro-structures facing each other, filling the middle with prepolymer, removing bubbles in the prepolymer under vacuum conditions, and curing to obtain a PDMS substrate with micro-groove structures on both surfaces;

[0011] S4, placing the PDMS substrate having microgroove structures on both surfaces obtained in step S3 in an alkaline Tris buffer solution containing dopamine hydrochloride, covering the lower surface with tape, and treating at room temperature for 12 to 30 hours, attaching a layer of polydopamine coating on the upper surface of the PDMS substrate having microgroove structures on both surfaces, rinsing and vacuum drying, to obtain sample A;

[0012] S5, placing the sample A obtained in step S4 in a curcumin-ethanol solution, attaching a layer of curcumin on the sample A, rinsing and vacuum drying, and obtaining a sample B;

[0013] S6. placing the sample B obtained in step S5 in a quaternary ammonium chitosan solution, coating the surface of the sample B with a layer of quaternary ammonium chitosan coating, rinsing and vacuum drying to obtain a curcumin-loaded Janus wound dressing.

[0014] Preferably, in step S1, the surface-smooth substrate is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, the ultrasonic frequency is 40 kHz, the ultrasonic power is 90-150 W, and the ultrasonic time is 5-10 min.

[0015] Preferably, in step S2, the specific processing parameters of the femtosecond laser are: wavelength of 1030nm, scanning speed of 500-1500μm / s, laser flux of 1-10J / cm 2 , scanning interval is 10~20μm, and pulse frequency is 50~150KHz.

[0016] Preferably, in step S2, the specific steps of the femtosecond laser processing are as follows:

[0017] (1) Fixing the clean substrate obtained in step S1 on a glass slide, moving it to a high-precision translation stage, and fixing it;

[0018] (2) Using multiple mirrors, the femtosecond laser is directed to the surface of the substrate to be processed. The computer controls the translation stage so that the laser focus after being focused by the objective lens falls vertically to the surface of the clean substrate, and a micro-groove array structure is prepared on the surface.

[0019] Preferably, in step S3, the prepolymer is a mixture of silicone elastomer prepolymer Sylgard 184A and silicone elastomer curing agent Sylgard 184B in a mass ratio of 10:1.

[0020] Preferably, in step S3, the specific conditions for removing bubbles in the prepolymer under vacuum conditions are: the vacuum degree is -0.8 to -1.2×10 5 Pa, the time is 20 to 40 minutes, the curing temperature is 70 to 100° C., and the curing time is 2 to 5 hours.

[0021] Preferably, in step S4, the pH of the alkaline Tris buffer containing dopamine hydrochloride is 8-10.

[0022] Preferably, in step S5, the sample A obtained in step S4 is placed in a curcumin-ethanol solution and treated in the dark at room temperature for 12 to 30 hours, a layer of curcumin is attached to the sample A, and the sample is rinsed and vacuum dried to obtain a sample B.

[0023] Preferably, in step S6, the sample B obtained in step S5 is placed in a quaternary ammonium chitosan solution, and is protected from light at room temperature for 12 to 30 hours, a quaternary ammonium chitosan coating is coated on the surface of the sample B, and the sample is rinsed and vacuum dried to obtain a curcumin-loaded Janus wound dressing.

[0024] The invention also provides a curcumin-loaded Janus wound dressing prepared by the preparation method.

[0025] The present invention also provides a curcumin-loaded Janus wound dressing prepared by the preparation method or use of the curcumin-loaded Janus wound dressing in the preparation of antibacterial drugs.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects:

[0027] The present invention discloses a femtosecond laser-based loaded curcumin Janus wound dressing and a preparation method. A PDMS film with a microgroove structure is prepared by femtosecond laser processing and a reverse molding process, which effectively improves the preparation efficiency. At the same time, the microgroove structure significantly improves the curcumin loading capacity, and its high specific surface area increases the contact area with curcumin, thereby increasing the drug loading of curcumin. The loaded curcumin Janus wound dressing has excellent cell compatibility, no cytotoxicity, can significantly regulate the growth of NIH / 3T3 cells, and provides a good cell growth environment for wound healing. In addition, one surface of the dressing is hydrophilic and the other surface is hydrophobic. This unique Janus structure enables the dressing surface to resist bacterial adhesion and drug-loaded killing of bacteria through the structure, and promotes the dual effects of cell growth, showing excellent antibacterial activity, and effectively accelerating wound healing.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the optical path diagram of femtosecond laser processing of the present invention;

[0030] Figure 2 This is a SEM image of the curcumin-loaded Janus wound dressing provided in Example 1 of the present invention, wherein: Figure 2 (a) is the SEM image of the micro-groove structure substrate surface. Figure 2 (b) is the SEM image of the outer layer of the Janus wound dressing loaded with curcumin. Figure 2 (c) is the SEM image of the inner layer of the Janus wound dressing loaded with curcumin;

[0031] Figure 3 The test results of the static water contact angle of the dressing provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 3 (a) is the original PDMS test result. Figure 3 (b) is the test result of the outer layer of the curcumin-loaded Janus wound dressing provided in Example 1. Figure 3 (c) is the test result of the curcumin dressing provided in Comparative Example 1, Figure 3 (d) is the test result of the inner layer of the curcumin-loaded Janus wound dressing provided in Example 1;

[0032] Figure 4 The cell activity test results of the dressings provided in Example 1 and Comparative Example 1 of the present invention;

[0033] Figure 5 Fluorescence microscope images of the dressings provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 5(a) is a fluorescence microscope image of NIH / 3T3 cells on the original PDMS film surface. Figure 5 (b) is a fluorescence microscope image of NIH / 3T3 cells on the outer layer of the curcumin-loaded Janus wound dressing of Example 1. Figure 5 (c) is a fluorescence microscope image of NIH / 3T3 cells of curcumin dressing in comparative example 1. Figure 5 (d) is a fluorescence microscopy image of NIH / 3T3 cells in the inner layer of the curcumin-loaded Janus wound dressing provided in Example 1;

[0034] Figure 6 Fluorescence confocal microscope images of Staphylococcus aureus colonization on the dressings provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 6 (a) is a fluorescence confocal microscope image of Staphylococcus aureus colonization on the original PDMS film surface. Figure 6 (b) is a fluorescence confocal microscope image of Staphylococcus aureus colonization on the outer layer of the curcumin-loaded Janus wound dressing in Example 1. Figure 6 (c) is a fluorescence confocal microscope image of Staphylococcus aureus colonization on the curcumin dressing of comparative example 1, Figure 6 (d) is a fluorescence confocal microscope image of Staphylococcus aureus colonization in the inner layer of the curcumin-loaded Janus wound dressing provided in Example 1;

[0035] Figure 7 Fluorescence confocal microscope images of Staphylococcus aureus colonization on the dressings provided in Example 1 and Comparative Example 1 of the present invention, wherein: Figure 7 (a) is a fluorescence confocal microscope image of E. coli colonization on the original PDMS film surface. Figure 7 (b) is a fluorescence confocal microscope image of E. coli colonization on the outer layer of the curcumin-loaded Janus wound dressing in Example 1. Figure 7 (c) is a fluorescence confocal microscope image of Escherichia coli colonization on the curcumin dressing in comparative example 1. Figure 7 (d) is a fluorescence confocal microscope image of Escherichia coli in the inner layer of the curcumin-loaded Janus wound dressing provided in Example 1;

[0036] Figure 8 These are images of mouse wounds treated with the curcumin-loaded Janus wound dressing provided in Example 1 on days 0, 3, 7, 10, and 13. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] In the present invention, unless otherwise specified, other test materials and instruments and equipment are conventional test materials in the art and can be purchased through commercial channels.

[0040] Example 1

[0041] This embodiment provides a method for preparing a curcumin-loaded Janus wound dressing based on femtosecond laser, comprising the following steps:

[0042] S1. Use anhydrous ethanol and deionized water to ultrasonically clean the surface of JGS2 quartz glass at 40kHz for 5 minutes, blow dry with an ear-cleaning bulb to obtain clean JGS2 quartz glass;

[0043] S2, (1) fix the clean JGS2 quartz glass obtained in step S1 on a glass slide, move it to a high-precision translation stage, and fix it;

[0044] (2) A femtosecond laser with a wavelength of 1030 nm was guided to the surface of a clean JGS2 quartz glass by a reflector, and a computer-controlled translation stage was used to make the laser focus focused by the objective lens fall vertically to the upper surface of the clean JGS2 quartz glass, and a micro-groove array structure was prepared on the surface, wherein the femtosecond laser scanning speed was 1000 μm / s and the laser flux was 5.53 J / cm 2 , scanning spacing of 15μm, pulse frequency of 100KHz, and quartz glass with micro-groove structure were obtained.

[0045] S3, take a piece of quartz glass with a micro-groove structure obtained in step S2 as a template, place it with the micro-groove structure side upward, fill it with prepolymer (organic silicone elastomer prepolymer Sylgard 184A and organic silicone elastomer curing agent Sylgard 184B are mixed in a mass ratio of 10:1), and then put another piece of quartz glass with a micro-groove structure obtained in step S2 as a template, place it with the micro-groove structure surface downward, and place it at room temperature and a vacuum degree of -1.0×10 5 Pa for 30 min, and then cured at 80 °C for 3 h to obtain a PDMS substrate with microgroove structures on both surfaces;

[0046] S4, placing the PDMS substrate with microgroove structures on both surfaces obtained in step S3 in an alkaline Tris buffer containing dopamine hydrochloride, wherein the concentration of dopamine hydrochloride is 2 mg / mL and the pH of the Tris buffer is 8.5, covering the lower surface with tape, and treating at room temperature for 24 hours, attaching a layer of polydopamine coating on the upper surface of the PDMS substrate with microgroove structure, rinsing with deionized water twice after the treatment, and using a vacuum drying oven at 40°C and a vacuum degree of -1.0×10 5 Pa conditions for 2 h to obtain sample A;

[0047] S5, placing the sample A obtained in step S4 in a 2 mg / mL curcumin-ethanol solution, treating it in the dark at room temperature for 24 h, attaching a layer of curcumin on the sample A, rinsing it with deionized water twice after the treatment, and using a vacuum drying oven at 40°C and a vacuum degree of -1.0×10 5 Pa conditions for 2 h to obtain sample B;

[0048] S6, placing the sample B obtained in step S5 in a quaternized chitosan solution, treating it in the dark at room temperature for 24 hours, coating the surface of the sample B with a layer of quaternized chitosan coating, rinsing it with deionized water twice after the treatment, and drying it in a vacuum oven at 40°C and a vacuum degree of -1.0×10 5 After treatment under Pa conditions for 2 h, curcumin-loaded Janus wound dressing was obtained.

[0049] Comparative Example 1

[0050] S1. Mix the silicone elastomer prepolymer Sylgard 184A and the silicone elastomer curing agent Sylgard 184B in a mass ratio of 10:1 and heat at room temperature and a vacuum degree of -1.0×10 5 The PDMS film was treated at 80 °C for 30 min and then cured at 80 °C for 3 h to obtain a PDMS film.

[0051] S2, the PDMS film obtained in step S1 was placed in an alkaline Tris buffer containing dopamine hydrochloride for 24 hours, wherein the concentration of dopamine hydrochloride was 2 mg / mL and the pH of the Tris buffer was 8.5. After the treatment, it was rinsed twice with deionized water and heated at 40°C and a vacuum degree of -1.0×10 5 Pa conditions for 2 h to obtain sample D;

[0052] S3, placing the sample D obtained in step S2 in a 2 mg / mL curcumin-ethanol solution, treating it in the dark at room temperature for 24 h, attaching a layer of curcumin on the sample D, rinsing it with deionized water twice after the treatment, and using a vacuum drying oven at 40 ° C and a vacuum degree of -1.0×10 5 Pa conditions for 2 h to obtain sample E;

[0053] S4, placing the sample E obtained in step S3 in a quaternized chitosan solution, protecting from light at room temperature for 24 hours, coating the surface of the sample E with a layer of quaternized chitosan coating, rinsing with deionized water twice after the treatment, and drying in a vacuum oven at 40°C and a vacuum degree of -1.0×10 5 Pa conditions for 2 h to obtain curcumin dressing.

[0054] The effects of the curcumin-loaded Janus wound dressing provided in Example 1 and the curcumin dressing provided in Comparative Example 1 were verified by the following experiments.

[0055] Figure 1 This is the optical path diagram of femtosecond laser processing in Example 1, Figure 1 It can be seen that 1 represents a beam splitter, 2 represents an aperture, 3 represents a beam splitter, 4 represents a reflector, 5 represents an aperture, 6 represents an aperture, 7 represents a reflector, 8 represents a reflector, 9 represents an aperture, 10 represents an aperture, 11 represents a reflector, 12 represents a reflector, 13 represents an aperture, 14 represents an aperture, 15 represents a beam splitter, 16 represents a translation stage and a computer, 17 represents a beam splitter, 18 represents a CCD, and 19 represents a white light source. The laser is guided from the laser to the surface of the material through multiple reflectors, and the focus is vertically focused on the surface of the substrate through the objective lens to perform surface micro-groove structure processing.

[0056] 1. The curcumin-loaded Janus wound dressing provided in Example 1 was characterized. The experimental scheme was as follows: After different samples were treated with gold spraying (1 min), the surface morphology of the samples was observed using a Regulus 8230 scanning electron microscope (Hitachi, Japan). Figure 2 .

[0057] Depend on Figure 2 As shown in (a), after femtosecond laser processing, a microgroove array structure is formed on the quartz glass template; Figure 2 As shown in Figure (b), after the mold is reversed, a micro-groove array structure complementary to the template structure is prepared on the PDMS film; Figure 2 As can be seen from Figure (c), after modification with polydopamine hydrochloride, curcumin and quaternized chitosan coating, particles are evenly distributed around the ridges on the PDMS surface.

[0058] 2. The static contact angle test was conducted on the surface of the material provided in Example 1. The specific test scheme is as follows: The surface wettability of the sample was tested using a video-based OCA 25 contact angle meter (Olympus, Japan), and the droplet size was 4 μL. Each sample was measured three times. The results are shown in the figure. Figure 3 .

[0059] Depend on Figure 3 It can be seen that the contact angles of the original PDMS film, the outer layer of the curcumin-loaded Janus wound dressing provided in Example 1, the curcumin dressing provided in Comparative Example 1, and the inner layer of the curcumin-loaded Janus wound dressing provided in Example 1 are 112.40°±2.97, 134.00°±0.85, 36.80°±5.66, and 47.4°±4.38, respectively. The quaternized chitosan coating contains hydrophilic quaternary ammonium salt groups, which effectively reduce the surface contact angles of PQ and PFQ and have good hydrophilicity.

[0060] 4. The cell activity test of the dressings provided in Example 1 and Comparative Example 1 was performed as follows: NIH / 3T3 cells were cultured at 2×10 4 The density of cells / well was inoculated in a 48-well plate, and then the sterilized samples (P, PF, PQ and PFQ, 5mm×5mm) were added and incubated in a CO2 incubator at 37°C and 5% CO2 for 12h, 24h and 48h respectively. After the incubation was completed, a medium containing 10% CCK-8 (Dojindo) was added to the well plate. After incubation for 1h, the absorbance value (OD) of the solution at 450nm after different incubation times was detected using an ELX808 microplate reader (Bio Tek, USA), and the cell survival rate was calculated. Each sample was measured 5 times.

[0061] The cell viability calculation formula is as follows:

[0062]

[0063] The results are as follows Figure 4 , wherein P is the NIH-3T3 cell survival rate of the original PDMS film; PF is the NIH-3T3 cell survival rate of the microgroove structure PDMS in Example 1; PQ is the NIH-3T3 cell survival rate of the curcumin dressing provided in Comparative Example 1; PFQ is the NIH-3T3 cell survival rate of the curcumin-loaded Janus wound dressing provided in Example 1.

[0064] Depend on Figure 4 It can be seen that after different samples were incubated with NIH-3T3 cell suspension for 12, 24 and 48 hours, the cell survival rates were all greater than 80%, indicating that all samples had good biocompatibility.

[0065] 5. The dressings provided in Example 1 and Comparative Example 1 were subjected to a cell proliferation test, and the cell morphology on the surface of the samples was observed under a fluorescence microscope. The specific test was as follows: a 5 mm × 5 mm sample was sterilized and placed at the bottom of a 48-well plate. NIH / 3T3 cells were cultured at 5 × 10 4The density of cells / well was inoculated on the sample surface, and after incubation for 24 h in a CO2 incubator at 37°C and 5% CO2, the cells on the sample surface were stained with phalloidin solution and DAPI dye (Thermo Fisher, USA), and the cell adhesion morphology on the sample surface was observed under a fluorescence confocal microscope (Zeiss, Germany). Figure 5 .

[0066] Depend on Figure 5 It can be seen that the number of NIH-3T3 cells adhering to the original PDMS surface and the microgroove PDMS surface is very small. The number of NIH-3T3 cells adhering to the PDMS surface loaded with curcumin coating in Comparative Example 1 increases, because its hydrophilic surface improves cell adhesion. In contrast, the surface of the NIH-3T3 cell adhesion and spreading area on the surface of the curcumin-loaded Janus wound dressing provided in Example 1 is the largest, the number of cells is the largest, and the skeleton extends along the groove in the direction of the microgroove, indicating that the curcumin-loaded Janus wound dressing prepared in the embodiment of the present invention can promote cell proliferation.

[0067] 6. The above dressings were tested for colonization and activity of Staphylococcus aureus and observed under a fluorescence confocal microscope. A 5 mm × 5 mm sample was sterilized and placed at the bottom of a 48-well plate. The bacterial solution was diluted to a density of 1 × 10 8 CFU / mL of Staphylococcus aureus were inoculated on the surface of the samples and incubated in a high temperature and high humidity biochemical test chamber at 37°C and 80% relative humidity for 24 hours. Then, the bacteria on the surface of the samples were stained with a mixture of SYTO-9 and PI (Biyuntian, China), and the colonization and activity of bacteria on the surface of the samples were observed using an LSM980 fluorescence confocal microscope. The proportion of live and dead bacteria on the surface of the samples was analyzed using Image J software. Each sample was measured three times. The results are shown in Figure 6 .

[0068] Depend on Figure 6It can be seen that the coverage rate of live bacteria (green) on the original PDMS surface is 50.22% ± 4.39, and the coverage rate of dead bacteria (red) is 0.01%. Escherichia coli is dispersed and colonized at various locations on the surface, and almost no death is observed. Example 1 The outer layer of the Janus wound dressing loaded with curcumin has a coverage rate of live bacteria (green) of 37.31% ± 1.70 and a coverage rate of dead bacteria (red) of 0.05% ± 0.01, indicating that the microgroove structure can reduce the number of Staphylococcus aureus. The coverage rate of live bacteria (green) on the surface of the curcumin dressing in Comparative Example 1 is 21.38% ± 1.48, and the coverage rate of dead bacteria (red) is 8.89% ± 2.38, because curcumin has a certain killing ability against Staphylococcus aureus. On the inner surface of the curcumin-loaded Janus wound dressing provided in Example 1, the coverage rate of live bacteria (green) was 9.07%±0.63, and the coverage rate of dead bacteria (red) was 20.05%±1.21, indicating that the synergistic effect of the microgroove structure and the drug coating effectively reduced the colonization of live Staphylococcus aureus and improved the killing ability of Staphylococcus aureus.

[0069] 7. The above dressings were tested for E. coli colonization and activity, and observed using a fluorescent confocal microscope. A 5 mm × 5 mm sample was sterilized and placed at the bottom of a 48-well plate. The bacterial solution was diluted to a density of 1 × 10 8 CFU / mL of Escherichia coli were inoculated on the surface of the samples and incubated in a high temperature and high humidity biochemical test chamber at 37°C and 80% relative humidity for 24 hours. Then, the bacteria on the surface of the samples were stained with a mixture of SYTO-9 and PI (Biyuntian, China), and the colonization and activity of bacteria on the surface of the samples were observed using an LSM980 fluorescence confocal microscope. The proportion of live and dead bacteria on the surface of the samples was analyzed using Image J software. Each sample was measured three times. The results are shown in Figure 7 .

[0070] Depend on Figure 7It can be seen that the coverage rate of live bacteria (green) on the original PDMS surface is 40.51% ± 1.20, and the coverage rate of dead bacteria (red) is 0.27% ± 0.02. Escherichia coli is dispersed and colonized at various locations on the surface, and almost no death is observed. Example 1 The outer layer of the Janus wound dressing loaded with curcumin has a coverage rate of live bacteria (green) of 13.26% ± 1.20 and a coverage rate of dead bacteria (red) of 1.38% ± 0.24, indicating that the microgroove structure can effectively reduce the adhesion of Escherichia coli. Comparative Example 1 The coverage rate of live bacteria (green) on the surface of the curcumin dressing is 29.00% ± 3.97, and the coverage rate of dead bacteria (red) is 7.00% ± 1.24, because curcumin has a certain killing ability against Escherichia coli. The inner layer of the curcumin-loaded Janus wound dressing provided in Example 1 had a live bacteria (green) coverage of 6.77%±1.19 and a dead bacteria (red) coverage of 9.73%±0.62, indicating that the microgrooves loaded with curcumin and the coating significantly reduced the colonization of live Escherichia coli.

[0071] 8. After constructing a wound model with a diameter of 8 mm on the back of C57 mice, the wound was treated with the curcumin-loaded Janus wound dressing provided in Example 1. The results are as follows: Figure 8 , wherein P is the mouse wound image of the original PDMS film; PF is the mouse wound image of the microgroove structure PDMS in Example 1; PQ is the mouse wound image of the curcumin dressing provided in Comparative Example 1; PFQ is the mouse wound image of the curcumin-loaded Janus wound dressing provided in Example 1.

[0072] Depend on Figure 8 It can be seen that after 13 days of treatment, the PDMS wound loaded with curcumin coating was basically closed, with the highest degree of healing, and the surface showed light pink granulation tissue, indicating that the curcumin-loaded Janus wound dressing prepared in Example 1 of the present invention effectively accelerated wound healing.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a femtosecond laser-based curcumin-loaded Janus wound dressing, characterized in that: The steps include: S1, ultrasonically clean the substrate, dry it, and obtain a clean substrate; S2, performing femtosecond laser processing on the clean substrate obtained in step S1 to obtain a substrate with a micro-groove structure; S3, taking two sheets of substrates with micro-groove structures obtained in step S2 as templates, stacking the surfaces with micro-structures facing each other, filling the middle with prepolymer, removing bubbles in the prepolymer under vacuum conditions, and curing to obtain a PDMS substrate with micro-groove structures on both surfaces; S4, placing the PDMS substrate having microgroove structures on both surfaces obtained in step S3 in an alkaline Tris buffer solution containing dopamine hydrochloride, covering the lower surface with tape, and treating at room temperature for 12 to 30 hours, attaching a layer of polydopamine coating on the upper surface of the PDMS substrate having microgroove structures on both surfaces, rinsing and vacuum drying, to obtain sample A; S5, placing the sample A obtained in step S4 in a curcumin-ethanol solution, attaching a layer of curcumin on the sample A, rinsing and vacuum drying, and obtaining a sample B; S6. placing the sample B obtained in step S5 in a quaternary ammonium chitosan solution, coating the surface of the sample B with a layer of quaternary ammonium chitosan coating, rinsing and vacuum drying to obtain a curcumin-loaded Janus wound dressing.

2. The preparation method according to claim 1, characterized in that: In step S2, the specific processing parameters of the femtosecond laser are: wavelength of 1030nm, scanning speed of 500-1500μm / s, laser flux of 1-10J / cm 2 , scanning interval is 10~20μm, and pulse frequency is 50~150KHz.

3. The preparation method according to claim 1, characterized in that: In step S3, the prepolymer is a mixture of silicone elastomer prepolymer Sylgard 184A and silicone elastomer curing agent Sylgard 184B in a mass ratio of 10:

1.

4. The preparation method according to claim 1, characterized in that: In step S3, the specific conditions for removing bubbles in the prepolymer under vacuum conditions are: vacuum degree is -0.8 to -1.2×10 5 Pa, the time is 20 to 40 minutes, the curing temperature is 70 to 100° C., and the curing time is 2 to 5 hours.

5. The preparation method according to claim 1, characterized in that: In step S4, the pH of the alkaline Tris buffer containing dopamine hydrochloride is 8-10.

6. The preparation method according to claim 1, characterized in that: In step S5, the sample A obtained in step S4 is placed in a curcumin-ethanol solution and treated in the dark at room temperature for 12 to 30 hours, a layer of curcumin is attached to the sample A, and the sample is rinsed and vacuum dried to obtain a sample B.

7. The preparation method according to claim 1, characterized in that: In step S6, the sample B obtained in step S5 is placed in a quaternary ammonium chitosan solution, and is protected from light at room temperature for 12 to 30 hours. A quaternary ammonium chitosan coating is coated on the surface of the sample B, and the sample is rinsed and vacuum dried to obtain a curcumin-loaded Janus wound dressing.

8. The curcumin-loaded Janus wound dressing prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the curcumin-loaded Janus wound dressing prepared by the preparation method according to any one of claims 1 to 7 or the curcumin-loaded Janus wound dressing according to claim 8 in the preparation of antibacterial drugs.